Atomic layer deposition fabricating of ceramic nanofiltration membranes for efficient separation of dyes from water. Issue 7 (31st January 2018) - Chen, He; Wu, Shanshan; Jia, Xiaojuan; Xiong, Sen; Wang, Yong
Abstract : To meet the strong need for highly efficient and controllable manufacturing methods to ceramic nanofiltration (NF) membranes, we use atomic layer deposition (ALD) to prepare NF membranes by tightening ultrafiltration (UF) membranes. We confine the ALD deposition of TiO2 to the near‐surface region of substrate UF membranes. The pores (∼5 nm) in the selective layers are progressively reduced, thus transforming the original UF membranes to NF ones at acceptable expense of permeability. A molecular‐weight‐cut‐off (MWCO) down to 890 Da is obtained after merely 40 cycles and the water permeability remains as high as 32 L·m −2 ·h −1 ·bar −1 . MWCOs can be flexibly tuned by altering ALD cycles, which is lowered down to 410 Da with 60 ALD cycles. The deposited membranes are used to remove dyes from water and they show significantly enhanced rejection to negatively charged dyes. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2670–2678, 2018